Relações entre parte aérea e raízes em povoamentos de teca - Behling, Maurel; Teles Arantes Felipe, Rafaella; Bento Farias, Jaqueline; de Carvalho, Géssica; Lima Neves, Júlio César (Revista Ceres, 2025)
There is little information available about teak leaves and roots in Brazil. The objectives of this work were to evaluate if the above-ground components, biomass, and leaf area are good biomass and root surface estimators in teak (Tectona grandis) stands. In the sampling, executed in 17- and 90-month-old teak trees established in commercial stands, the roots, stem, branches, and leaves were separated to determine the dry biomass and specific leaf area (SLA) and specific root area (SRA). The leaf surface of a young tree was four times larger than the surface of an adult teak tree leaf. The fine roots surface (< 2 mm) was four times larger than the medium roots surface (2 to 5 mm) in adult trees. In these stands, on average, SLA was 13.14 m² kg-1 and SRA was 13.86 m² kg-1, indicating similar C use efficiency in the production of surfaces for acquisition of resources (solar radiation, water, and nutrients) and suggesting that there was synchrony in the C allocation for leaves and roots. The leaf area index was 1.2 m2 m-2 in the young plants and 8.3 m2 m-2 in the adult plants. Leaf area and above-ground biomass have strong relationship with fine and middle roots area and root biomass, reflecting the carbon allocation patterns of trees at the age that they were assessed. Leaf area is a good estimator of the surface area of teak roots.